ROCK MASS RATING AND GEOLOGICAL STRENGTH INDEX OF ROCK MASSES OF INDONESIA COAL MINING AREAS - Singgih Saptono; M. Rahman Yulianto; Vega Vergiagara; Herry Sofyan (Jurusan Teknik Informatika, 2020)
AbstractRock slope stability is important for the safety of personnel and equipment in open pit mines. Slope instability and failure occurs due to many factors such as adverse slope geometries, geological discontinuities, weak or weathered slope materials. External loads such as high rainfall and seismicity can play an important role in slope failure. For this reason, it is necessary to classify the rock mass accurately against a rock mass as the basis for determining the technical policy of the rock mass. Rock slopes in open-pit coal mining areas, especially in Indonesia, are characterized by applying various rock mass classification systems, such as the Rock Mass Rating (RMR) and Geological Strength Index (GSI), because the study area consists of well exposed rock formations. In the RMR system, there are five main parameters namely. Uniaxial Compressive Strength (UCS) of rocks, Rock Quality Designation (RQD), discontinuity distances, discontinuity conditions, and groundwater conditions are considered. In this paper, several rock mass classification systems developed for the assessment of rock slope stability are evaluated against rock slope conditions in the tropics, namely the Indonesian region, especially in sedimentary rocks in coal-open mining areas. So that the corrected GSI equation is obtained which is used to characterize rock slopes based on the quantitative analysis of the rock mass structure and the surface conditions of the discontinuity.Keywords : RMR, GSI, UCS, Rock, Quality, DesignationStabilitas lereng batuan penting untuk diperhatikan bagi keselamatan personel dan peralatan di tambang terbuka. Ketidakstabilan dan kegagalan lereng terjadi karena banyak faktor seperti geometri lereng yang merugikan, diskontinuitas geologis, material lereng yang lemah atau lapuk akibat pengaruh cuaca. Beban eksternal seperti curah hujan yang tinggi dan kegempaan dapat memainkan peran penting dalam kegagalan lereng. Untuk itu diperlukan klasifikasi massa batuan secara tepat terhadap suatu massa batuan sebagai dasar penentuan kebijakan teknis terhadap massa batuan tersebut. Lereng batuan di daerah tambang terbuka batubara khususnya di Indonesia, dikarakterisasi dengan menerapkan berbagai sistem klasifikasi massa batuan, seperti Rock Mass Rating (RMR) dan Geological Strength Index (GSI), karena daerah penelitian terdiri dari formasi batuan yang terekspos dengan baik. Dalam sistem RMR, terdapat lima parameter utama yaitu. Uniaxial Compressive Strength (UCS) dari batuan, Rock Quality Designation (RQD), jarak diskontinuitas, kondisi diskontinuitas, dan kondisi air tanah dipertimbangkan. Dalam makalah ini, beberapa sistem klasifikasi massa batuan yang dikembangkan untuk penilaian stabilitas lereng batuan dievaluasi terhadap kondisi lereng batuan pada daerah tropis yaitu wilayah Indonesia, khususnya pada batuan sedimen di wilayah tambang terbuka batubara. Sehingga didapatkan persamaan GSI terkoreksi yang digunakan untuk mengkarakterisasi lereng batuan berdasarkan analisis kuantitatif struktur massa batuan dan kondisi permukaan dari diskontinuitas.Kata Kunci : RMR, GSI, UCS, Rock, Quality, Designation